The assessment of the attitude of the students of the 5th year of the medical faculty concerning the specialization in family medicine and the state of knowledge on the functioning of Primary Health Care - Jankowska, Paula; Jankowski, Krzysztof; Kamiński, Piotr; Rudnicka-Drożak, Ewa; Zajdel, Dominika (Journal of Education, Health and Sport, 2019)
Introduction: Family Medicine is a relatively new specialisation in Poland, that was created to increase availability of comprehensive medical care near the place of residence. Due to the major deficiency of human resources there is a huge need of educating medical personnel. Objectives: This study is an evaluation of knowledge level and attitudes towards family medicine specialisation of The Lublin Medical University Medical Faculty 5th year students, starting their family medicine classes. Results: Among the respondents 1.49% declared willingness to start family medicine specialisation, 40.89% is considering this career path, 39.03% is not considering this career path, 18.59% is definitely not considering this specialisation. Main factors, which are the reasons why students consider undertaking family medicine specialisationwere: flexible working hours (79.82%), wide range of patient’s ailments (78.07%), no on-call time (73.68%). On the other hand, students consider job in PHC as monotonous and hardly prestigious and 94.1% of respondents assessed that cooperation of family physicians with other specialisations is average at best. Only 13% correctly indicated what are the factors the amount of money per patient depends on. Majority of students correctly named family physicians’ responsibilities and medical examinations that family physician can perform under the agreement with National Health Fund. Conclusion:Research gathered in this document indicate on little interest in family medicine specialisation among students and at the same time on lack of certain knowledge about job in PHC. Thus, there is a need to create relevant educational programmes which would turn future doctor’s attention to general practice.